Analisis Dampak Konten Visual terhadap Kesejahteraan Psikologis pada Media Sosmed Instagram - Lola Nurhasanah; Tata Sutabri (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2024)
This study aims to analyze the impact of visual content on Instagram on users’ psychological well-being, focusing on body image, Fear of Missing Out (FoMO), and life satisfaction. As Instagram usage increases, more users are exposed to visual content promoting certain beauty standards and ideal lifestyles that are often unattainable for many. This exposure drives social comparison and FoMO, triggering various adverse effects on psychological well-being, such as low self-confidence, anxiety, and dissatisfaction with oneself. This research employed survey methods and a literature review from relevant prior studies. Findings indicate that exposure to idealized visual content on Instagram significantly intensifies body image dissatisfaction and personal insecurity. On the other hand, findings also suggest that educational and inspirational content on Instagram has the potential to support psychological well-being, though its accessibility and popularity are often overshadowed by entertainment and lifestyle content. The study concludes by emphasizing the need for users to be more selective in their content consumption and the platform’s role in promoting positive content that supports psychological well-being. This approach